2006
DOI: 10.2535/ofaj.83.73
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Lingual Papillae in the Raccoon Dog and Fox

Abstract: Summary: The dorsal lingual surfaces of the raccoon dogs (Nyctereutes procyonoides) and fox (Vulpes vulpes japonica) were examined by scanning electron microscopical (SEM) observations. The distribution and type of the lingual papillae found in the raccoon dog were similar to those in the fox. Filiform, fungiform, foliate and vallate papillae were observed. The filiform papillae were distributed over the entire dosal surface of the tongue. Each filiform papilla on the apical surface of the tongue had several p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
73
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(98 citation statements)
references
References 11 publications
(16 reference statements)
22
73
2
1
Order By: Relevance
“…The lingual median prominence was a characteristic feature in some mammals, which agree with our observation in New Zealand white rabbit tongue, and in; bank vole (Jackowiak & Godynicki, 2005), rabbit (Nonaka et al, 2008) and herbivorous artiodactylas (Zheng & Kobayashi, 2006), while omnivorous artiodactylas (pig) and carnivores animals not have a lingual prominence (Emura et al, 2006;Kumar & Bate, 2004). While (Pastor et al, 1993) in common European bat reported that there was a prominent of intermolar tubercle, moreover, molossid bats have a prominent mid-dorsal lobe as noted by Gregorin (2003), but Emura et al (2001b), Jackowiak et al (2009), Gregorin and Mqokeli & Downs (2012) reported that, there is no typically intermolar tubercle in all bats, while our study in the Egyptian fruit bat noted that, the characteristic feature of the dorsal surface of the middle part of tongue is the presence of a shallow intermolar tubercle, located close to the posterior half area of the tongue.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lingual median prominence was a characteristic feature in some mammals, which agree with our observation in New Zealand white rabbit tongue, and in; bank vole (Jackowiak & Godynicki, 2005), rabbit (Nonaka et al, 2008) and herbivorous artiodactylas (Zheng & Kobayashi, 2006), while omnivorous artiodactylas (pig) and carnivores animals not have a lingual prominence (Emura et al, 2006;Kumar & Bate, 2004). While (Pastor et al, 1993) in common European bat reported that there was a prominent of intermolar tubercle, moreover, molossid bats have a prominent mid-dorsal lobe as noted by Gregorin (2003), but Emura et al (2001b), Jackowiak et al (2009), Gregorin and Mqokeli & Downs (2012) reported that, there is no typically intermolar tubercle in all bats, while our study in the Egyptian fruit bat noted that, the characteristic feature of the dorsal surface of the middle part of tongue is the presence of a shallow intermolar tubercle, located close to the posterior half area of the tongue.…”
Section: Discussionsupporting
confidence: 90%
“…As in the previous published data, the lingual papillae were species-specific, in which differing in their number among mammalian species, these differences may depend on dissimilarities in diet, feeding habits and handling of food in mouth (Emura et al, 2002b;Abumandour & El-Bakary), the previous data clear in; our study in Egyptian fruit bat, this confirmed by presence of four types of lingual papillae; two mechanical and two gustatory as noted in; bats (Selim et al, 2008;Abumandour & El-Bakary;Abayomi et al, 2009), moreover other mammals have four lingual papillae; as in our study in New Zealand white rabbits; one mechanical (filiform) and three gustatory (fungiform, foliate and circumvallate) as noted in; rats (Nasr et al, 2012), bank vole (Jackowiak & Godynicki, 2005), dog and fox (Emura et al, 2006). However, three types of lingual papillae; one mechanical (filiform) and two gustatory (fungiform and circumvallate) as noted in; bats (Pastor et al, 1993;Emura et al, 2001b;Park & Lee, 2009;Masuko et al, 2007), however, there were two types only of papillae (filiform and fungiform) in hematophagous bats (Masuko et al).…”
Section: Discussionsupporting
confidence: 80%
“…Similar SEM studies have been reported on the dorsal lingual surface of the other mammals (Emura et al, 2000(Emura et al, , 2003(Emura et al, , 2004(Emura et al, , 2006Jackowiak and Godynicki, 2004).…”
Section: Discussionsupporting
confidence: 80%
“…Some vallate papillae of the asian black bear were composed by a primary papillae which was divided into several secondary papillae by intermediate grooves (Emura et al, 2001). The dorsal surfaces of the vallate papillae in the tiger, raccoon dog and fox were irregular (Emura et al, 2004(Emura et al, , 2006. The surfaces of the vallate papillae in the silver fox were smooth (Jackowiak and Godynicki, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation